Comparison of two joint-preserving treatments for osteonecrosis of the femoral head: core decompression and core decompression with additional cancellous bone grafting - Wörner, Michael; Voelkl, Korbinian; Bliemel, Christopher; Ferner, Felix; Weber, Markus; Renkawitz, Tobias; Grifka, Joachim; Craiovan, Benjamin (The journal of international medical research, 2023)
Objective - Femoral head necrosis (FHN) affects mostly young and active people. The most common operative therapy is core decompression (CD) with optional cancellous bone grafting (CBG). Because little information is available on the long-term results of these procedures, we investigated the effectiveness of CD and CD + CBG in patients with ARCO stage II FHN in terms of postoperative pain, range of motion, patient-reported outcome measures (Harris Hip Score, Hip Disability and Osteoarthritis Outcome Score, EuroQol 5D, and Short Form 36 Questionnaire), and disease progression. - Methods - We retrospectively compared 11 patients treated with CD alone 48.0 months (range, 26.3-68.5 months) postoperatively versus 11 patients treated with CD + CBG 69.2 months (range, 38.0-92.9 months) postoperatively. All patients were assessed according to a routine clinical protocol involving a clinical examination, questionnaires, and radiological imaging (X-ray and magnetic resonance imaging). - Results - The clinical and radiological results showed no significant differences between the two groups. Both interventions demonstrated equal results according to clinical scores. - Conclusions - Our data may encourage application of the less invasive technique of CD alone without CBG, which is more surgically demanding. Further prospective studies with longer follow-up are necessary to clarify the risk factors for therapy failure.
Zuerst online veröffentlicht: 10. August 2023
Gesehen am 02.10.2023